Reasoning of additional diagnostic parameters for electric insulation diagnostics by absorption methods - Kyrylenko, V.M.; Kyrylenko, K.V.; Budko, M.O.; Denysiuk, P.L. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2021)
The aim of this work is to analyze the inadequacies of the diagnostic parameters, in particular the absorption and polarization coefficients, which are manifested in their integral character and dependence on the ratio of values of several elements of the equivalent scheme of insulation replacement. This article contains the results of theoretical investigation of the extremе nature of the absorption diagnostic parameters, which leads to unambiguity of the diagnostics procedure. The ways of partial adjustment of this unambiguity have been proposed. Methodology. To determine the extremality of the absorption coefficients depending on the absorption time, absorption capacity and resistance, as well as the leakage resistance, the usual method of investigating the functions was used, detailed calculations have been obtained by using MATLAB software. Results. Has been shown that the ambiguity of diagnostic results is caused by the contradiction of the integral character of the diagnostic parameters and the local character of the isolation failures, in particular breakdown, by ambiguous dependence of the diagnostic parameters on the values of the elements of the insulation replacement scheme and the extremal nature of the diagnostic parameters. Based on the general expression describing all currently used absorption coefficients, it is shown that they all have an extremum, the value of which depends on the parameters of the insulation substitution scheme and the time interval between the measurements of the absorption current. The dependence of the extreme value of the absorption and polarization coefficients on the parameters of the insulation substitution scheme has been established. Has been shown that to eliminate the ambiguity caused by the extremity of the absorption coefficients, it is necessary to introduce additional diagnostic parameters, such as the ratio of leakage resistance to absorption resistance, as well as the critical value of the absorption time constant. Originality. The detailed analysis of the reasons of ambiguity of electric insulation technical diagnostics by absorption methods has been carried out. A method for eliminating the ambiguity caused by the extremity of the absorption coefficients has been proposed. Practical significance. To eliminate the ambiguity caused by the extremity of the absorption coefficients, additional diagnostic parameters are proposed – the ratio of leakage resistance to the absorption resistance and critical values of the absorption time constant. The applying of these parameters with the absorption coefficients will more adequately assess the technical condition of insulation.